2002
DOI: 10.1007/s100720200017
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on Alzheimer’s disease and exposure to anesthesia

Abstract: Aretrospective hospital-based case-control study was performed with the aim to evaluate the association between exposure to anesthesia and Alzheimer's disease (AD). A total of 115 AD patients, 230 Parkinson's disease (PD) patients and 230 patients with non-degenerative neurological disease were studied. Each AD case was matched for sex, age (+/-3 years) and geographic area of residence with four controls (2 PD patients and 2 with other neurological disease). Information about exposure to general anesthesia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 16 publications
1
73
2
2
Order By: Relevance
“…But the study of a sufficiently large cohort, including cognitively impaired people, with a broad interquartile range extending beyond the age of 80 years, could be valuable. We note that several of the studies that failed to find a relevant association 15, 33, 35, 39, but not all 34, 36, had a substantial proportion of participants who had surgery when < 70 years old. As the definition of the vulnerable population(s) is refined, some of the apparent contradictions above may be explained.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…But the study of a sufficiently large cohort, including cognitively impaired people, with a broad interquartile range extending beyond the age of 80 years, could be valuable. We note that several of the studies that failed to find a relevant association 15, 33, 35, 39, but not all 34, 36, had a substantial proportion of participants who had surgery when < 70 years old. As the definition of the vulnerable population(s) is refined, some of the apparent contradictions above may be explained.…”
Section: Discussionmentioning
confidence: 68%
“…More studies have investigated associations of surgery or anaesthesia with either dementia 20, 21, 33, 34, 35, 36 or Alzheimer's disease 33, 37, 38, 39, 40. Several 20, 21, 38, 40 have reported increased risks for these outcomes, but several have not 33, 34, 35, 36, 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasparini and coauthors also performed a retrospective case-controlled study of AD patients. In their study, the controls were Parkinson disease patients and patients with other neurological diseases 141 -but a link between general anesthesia and other neurological diseases has been hypothesized, 132 such that lack of a difference in anesthetic exposure between AD patients and patients with Parkinson or other neurological diseases does not imply a lack of a deleterious effect of anesthetic exposure.…”
Section: Anesthesia and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Molecular mechanisms were hypothesized and especially volatile anesthetics were demonstrated to be associated with Aβ production, Aβ oligomerization, Tau formation and Tau phosphorylation as described thoroughly in a review by Papon et al 56 Several observational studies were designed to substantiate these experimental theories with epidemiological data. 32,47,48,[57][58][59][60] Nonetheless, a recent systematic review concluded that, despite the amount of studies available, evidence for an association of anesthesia with AD is Selected were those possibly associated with AD induction by a potentially transmissible pathogen (e.g., viral infections, blood transfusion, cns surgery). Therefore, studies regarding anesthesia, peripheral surgery, life style factors, genetics, etc., which are more abundant, are not shown.…”
Section: Experimental Cluesmentioning
confidence: 99%